Synthesis and characterization of Co(II), Ni(II), Cu(II), and Zn(II) complexes with a new vic-dioxime (E,E)-N?-hydroxy-2-(hydroxyimino)-N-(4-{[(2-phenyl-1,3-dioxolan-4yl)methyl]amino}butyl)ethanimidamide - Canpolat, E; Kaya, M; Yazici, A (Maik Nauka/Interperiodica, 2004)
A new vic-dioxime ligand containing 1,3-dioxolane ring and 1,4-diaminobutane, (E,E)-N'-hydroxy-2-(hydroxyimino)-N-(4-{ [(2-phenyl-1,3-dioxolan-4-yl)methyl]amino}butyl)ethanimidamide (H2L) and the metal mononuclear complexes with a I : 2 and I : I metal-ligand ratio have been prepared with chloride salts Co(II), Ni(II), Cu(II), and Zn(II) in EtOH. The structures of the ligand and its complexes have been established by microanalyses, IR, UV-VIS, H-1 and C-13 NMR spectra, elemental analyses, and conductivity and magnetic susceptibility measurements. Also their thermal behavior has been studied by the TGA analysis.
Keywords: Transition-Metal-Complexes; 3,8-Dimethyl-5,6-Benzo-4,7-Diazadeca-3,7-Diene-2,9-Dione Dioxime; (Non-Alkyl)Cobalt(Iii) Complexes; Coenzyme-B12 Models; Crystal-Structure; Ligands; Reactivity; Cobalt; Oxime; Vitamin-B12